Effects of stocking density on the growth and breeding performance of broodfish and larval growth and survival of shol, Channa striatus (Bloch) (Journal of the Bangladesh Agricultural University, 2010)
Two experiments were conducted with a view to assessing the effects of stocking densities on the growth and breeding performance and larval growth and survival of Channa striatus. The first one was carried out with a view to find a suitable stocking density of Channa striatus at which they could spawn while the second experiment dealt with the effect of stocking density on growth and survival of the produced larvae. The first experiment was carried out in nine equal-sized chambers of raceway separated by netted wooden frame with an area of 1.83 ×1.12m2 each. The effective water depth in each of the raceway chambers was maintained at 1.2m. The broodfish were stocked at 4 (357.22g/m2), 6 (541.78g/m2) and 8 (719.18g/m2) at 1:1 male-female ratio and fed with washed and chopped poultry viscera twice a day and with live silver carp fry twice a week. No significant (P>0.05) difference in weight and specific growth rate was observed among the broodfish reared under different stocking densities during the experimental period of 80 days. The broodfish stocked at a density of 357.22g/m2 and 541.78g/m2 spawned naturally in their respective chambers. The fish stocked at 541.78g/m2 showed the best breeding performance. The second experiment was carried out with 4-5 days old larvae in 9 bowls of 10l capacity divided into three treatments having 20, 40 and 60 larvae each i.e. the stocking density were of 2, 4 and 6 larvae/l respectively. Larvae of treatment I which was stocked with 2 larvae/l showed significantly higher growth rate from the 7th day of the experiment and maintained the same trend up to the end of the experiment (i.e. 21st day) compared to other treatments. Larvae of treatment I also showed significantly higher health condition (13.31±0.69mg/mm) and survival rate (80.00±3.00) compared to those of the other two. Keywords: Stocking density; growth rate; survival rate; breeding performance; Channa striatus. DOI: 10.3329/jbau.v7i2.4756 J. Bangladesh Agril. Univ. 7(2): 427-432, 2009